Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure! Let's go through the process of simplifying the given expression step by step.
We start with the expression:
[tex]\[ \left(\frac{a^2 b^{-5} c^3}{a^{-2} c^{-4}}\right)^4 \][/tex]
First, we simplify the fraction inside the parentheses. We do this by combining the exponents for each variable. Using the properties of exponents, we have:
[tex]\[ \frac{a^2 b^{-5} c^3}{a^{-2} c^{-4}} = a^{2 - (-2)} \cdot b^{-5} \cdot c^{3 - (-4)} \][/tex]
Simplify the exponents:
[tex]\[ a^{2 - (-2)} = a^{2 + 2} = a^4 \][/tex]
[tex]\[ c^{3 - (-4)} = c^{3 + 4} = c^7 \][/tex]
Thus, the expression inside the fraction becomes:
[tex]\[ a^4 \cdot b^{-5} \cdot c^7 = \frac{a^4 c^7}{b^5} \][/tex]
So the given expression now looks like:
[tex]\[ \left(\frac{a^4 c^7}{b^5}\right)^4 \][/tex]
Next, we apply the exponent 4 to each term inside the parentheses:
[tex]\[ \left(\frac{a^4 c^7}{b^5}\right)^4 = \frac{(a^4)^4 (c^7)^4}{(b^5)^4} \][/tex]
Simplify the exponents:
[tex]\[ (a^4)^4 = a^{4 \cdot 4} = a^{16} \][/tex]
[tex]\[ (c^7)^4 = c^{7 \cdot 4} = c^{28} \][/tex]
[tex]\[ (b^5)^4 = b^{5 \cdot 4} = b^{20} \][/tex]
So the expression becomes:
[tex]\[ \frac{a^{16} c^{28}}{b^{20}} \][/tex]
Therefore, the simplified form of the expression using only positive exponents is:
[tex]\[ \boxed{\frac{a^{16} c^{28}}{b^{20}}} \][/tex]
We start with the expression:
[tex]\[ \left(\frac{a^2 b^{-5} c^3}{a^{-2} c^{-4}}\right)^4 \][/tex]
First, we simplify the fraction inside the parentheses. We do this by combining the exponents for each variable. Using the properties of exponents, we have:
[tex]\[ \frac{a^2 b^{-5} c^3}{a^{-2} c^{-4}} = a^{2 - (-2)} \cdot b^{-5} \cdot c^{3 - (-4)} \][/tex]
Simplify the exponents:
[tex]\[ a^{2 - (-2)} = a^{2 + 2} = a^4 \][/tex]
[tex]\[ c^{3 - (-4)} = c^{3 + 4} = c^7 \][/tex]
Thus, the expression inside the fraction becomes:
[tex]\[ a^4 \cdot b^{-5} \cdot c^7 = \frac{a^4 c^7}{b^5} \][/tex]
So the given expression now looks like:
[tex]\[ \left(\frac{a^4 c^7}{b^5}\right)^4 \][/tex]
Next, we apply the exponent 4 to each term inside the parentheses:
[tex]\[ \left(\frac{a^4 c^7}{b^5}\right)^4 = \frac{(a^4)^4 (c^7)^4}{(b^5)^4} \][/tex]
Simplify the exponents:
[tex]\[ (a^4)^4 = a^{4 \cdot 4} = a^{16} \][/tex]
[tex]\[ (c^7)^4 = c^{7 \cdot 4} = c^{28} \][/tex]
[tex]\[ (b^5)^4 = b^{5 \cdot 4} = b^{20} \][/tex]
So the expression becomes:
[tex]\[ \frac{a^{16} c^{28}}{b^{20}} \][/tex]
Therefore, the simplified form of the expression using only positive exponents is:
[tex]\[ \boxed{\frac{a^{16} c^{28}}{b^{20}}} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.